DSSHerbicide: Weed control in winter wheat with a decision support system in three South Baltic regions – Field experimental results. (October 2015) - Sønderskov, M.; Fritzsche, R.; de Mol, F.; Gerowitt, B.; Goltermann, S.; Kierzek, R.; Krawczyk, R.; Bøjer, O.M.; Rydahl, P.
Abstract: DSSHerbicide Germany and DSSHerbicide Poland are two decision support systems (DSS) developed for weed control in winter wheat in Northern regions of Germany and Poland. DSSHerbicide is based upon an existing Danish DSS, Crop Protection Online (CPO). Herbicide recommendations from DSSHerbicide are based on efficacy estimates from a dose–response model and required weed control levels defined by expert evaluations and practical experience. DSSHerbicide was parameterised for 22 commonly occurring weed species and 48 herbicides in Poland and for 23 weed species and 32 herbicides in Germany. Validation trials were conducted in Poland, Germany and Denmark primarily in private farmer's winter wheat fields. This enabled a comparison between the herbicide use with standard recommendations and with the existing Danish CPO and the German and Polish DSSHerbicide. Differences among herbicide applications were analysed based on the treatment frequency index (TFI, relation of actually applied dose to label rate) and the costs of herbicide treatments. Recommendations from DSSHerbicide resulted in lower herbicide use than standard recommendations from advisory services in Germany and Poland. TFI of autumn applications from DSSHerbicide recommendations were lower than standard recommendations. The spring application, however, did not differ among herbicide treatments. Yield and weed coverage, estimated by visual observations, were measured at harvest. The TFI of recommendations from DSSHerbicide, measured over the whole growing season, were approximately 20 and 40% lower than standard recommendations in Germany and Poland, respectively. Yields or weed coverage did not differ among sprayed treatments at harvest. All herbicide treatments improved yield and lowered weed coverage compared to controls of no herbicide application. The cost for the chosen herbicides did not differ among treatments, but this is considered a consequence of the limited herbicide choices in these new DSS prototypes. DSSHerbicide provided equally robust recommendations as the existing Danish CPO, and indicated a potential for herbicide reductions in Germany and Poland compared to the reference standard recommendations. As the present DSSHerbicide versions for Germany and Poland are prototypes, fields trials providing data for parameterisation of more weed – herbicide relationships are required to implement additional herbicides in the systems. Highlights: DSSHerbicide are decision support systems for weed control in winter wheat in Northern parts of Germany and Poland. DSSHerbicide build on herbicide dose models and expert evaluated requirements for weed control. DSSHerbicide recommendations maintained yield compared to standard advice. DSSHerbicide recommendations resulted in equally high weed control compared to standard recommendations. A potential for herbicide use reductions was identified in German and Polish trials compared to standard recommendations.